Edukasi dan Praktik Pembuatan MPASI dalam Rangka Pencegahan Stunting di Kelurahan Sangasanga Dalam Kutai Kartanegara: Education and Practice of Making Breastfeeding in Order to Prevent Stunting in Sangasanga Dalam Kutai Kartanegara - Sawitri, Endang; Sari, Vivi Arsi Rahmania; Hafidhuddin, Muhammad Abdul Aziz; Atika, Andi Rafika; Saputri, Ni Made Maharani Indira; Diastuti, Denti; Wijaya, Joseffine Valentina; Wirayuda, M. Ade; Pramesti, Nadya Ashiilah Syifa; Maharani, Kinanti Nur Cantika; Dewi, Januartha Kisari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Stunting, a condition resulting from chronic malnutrition and recurrent infections, is a serious threat to child growth and development. Sangasanga Dalam Village, located in Kutai Kartanegara Regency, faces a high prevalence of stunting with 39 cases in June 2023. This study aims to increase the knowledge of posyandu cadres regarding complementary feeding as an effort to prevent stunting. By involving 29 posyandu cadres, counseling activities and the practice of making complementary foods were carried out at Wisma Ria Pertamina EP Sangasanga Field. Pre-tests and post-tests were conducted to measure the cadres' knowledge before and after the intervention. The results of statistical analysis showed a significant increase in the cadres' knowledge after the intervention, with a p-value <0.05. The enthusiasm of the cadres was evident from the attendance of 29 participants, exceeding the initial target of 20 cadres. The interactive learning process involved a nutritionist from Sangasanga Dalam Health Center, who provided a detailed understanding of making complementary food according to the age of the child. This study concludes that the SIAP-MPASI activity succeeded in increasing the knowledge of posyandu cadres about complementary food. The approach of counseling and practice with nutritionists proved effective in improving the cadres' understanding. Therefore, stunting prevention efforts can be improved in Sangasanga Dalam Village.